Rebuilding local seed system and safeguarding conservation of agrobiodiversity in the aftermath of Nepal 2015 earthquake - Gauchan, D.; Joshi, B.K.; Ghimire, K.H.; Poudyal, K.; Sapkota, Suraj; Sharma, S.; Dangol, D.M.S.; Khatiwada, S.; Gautam, S.; Sthapit, S.R. (Government of Nepal, Ministry of Agricultural Development, Food Security and Environmental Division, 2018)
A study was conducted from July 2015 to December 2017 to rebuild local seed system and safeguard conservation of agrobiodiversity in the aftermath of earthquake through rescue collection, conservation and repatriation of endangered crop landraces from 10 earthquake affected districts. The process employed several methods, approaches and processes combining rescue missions with qualitative and quantitative assessments techniques and tools. The process helped to assess status of diversity of traditional crops, identify endangered, extinct and rare crop landraces, document and characterize their unique agronomic traits and develop and validate methodology for conservation of native crops by linking on-farm and ex-situ approaches. A total of 921 accessions of 61 crops were collected from 35 VDCs of 10 severally earthquake affected districts. The process has identified 104 lost crop landraces and rescued 284 rare and endangered ones and conserved them in national Genebank. Some of the farmer demanded crop landraces are repatriated back to local communities and also conserved in community seed banks in affected districts.The process therefore helped to restore lost diversity, revive and strengthen the local seed system and safeguard biodiversity of native crops to adapt to more extreme and changing climatic condition